SISTEM INFORMASI MONITORING STOK MOTOR LISTRIK ALAT PRODUKSI BERBASIS MOBILE ANDROID - Muhamad Alda (Universitas Methodist Indonesia, 2023)
PT. Musim Mas is a business entity engaged in the processing of palm oil and soap in the city of Medan. In carrying out the processing, PT. Musim Mas uses several means of production. Every production tool used requires an electric motor to drive the tool, so PT. Musim Mas must provide stock of the electric motorbikes that will be used. In processing electric motor stock data, PT. Musim Mas still uses the manual method. Electric motor stock data is recorded and processed in a book by officers. In this way, the problem persists. Recording and processing data requires a significant investment of time and effort on the part of staff. The author conducted research to design an Android-based mobile information system that can be used to process and record electric motor stock. The waterfall method is used for system development, while the Kodular framework and Airtable database are used to build information systems. With this information system, it can help the warehouse staff of PT. Musim Mas in processing and recording as well as facilitate monitoring the stock of electric motor online via an Android smartphone.